2014
DOI: 10.2967/jnumed.113.131847
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Metabolic Tumor Volume and Total Lesion Glycolysis on Preoperative 18F-FDG PET/CT in Patients with Pancreatic Cancer

Abstract: In this study, we aimed to assess the prognostic value of metabolic tumor volume (MTV) and total lesion glycolysis (TLG) measured on 18 F-FDG PET/CT in pancreatic cancer patients who underwent resection with curative intent. Methods: Eighty-seven patients with pancreatic ductal adenocarcinoma who underwent 18 F-FDG PET/ CT and subsequent surgical resection with curative intent with (30 patients) or without (57 patients) neoadjuvant therapy were retrospectively enrolled. The maximum standardized uptake value (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
108
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(121 citation statements)
references
References 28 publications
10
108
3
Order By: Relevance
“…Results from recent studies demonstrate that MTV and TLG were computed using a maximum percentage threshold of 40-50% (30,31). However, other studies used a fixed SUV threshold, most commonly SUV2.5, where SUV>2.5 is the absolute threshold (TLG2.5 or MTV2.5), particularly for segmentation of lung tumors (32–34). Increasing interest in volumetric indices has led to the development of commercially available tools, for example PETVCAR, which enables the rapid and simple measurement of numerous indices for tumor analysis, including various threshold values of MTV and TLG (typically, 41-70% of SUV max within the tumor) (35).…”
Section: Discussionmentioning
confidence: 99%
“…Results from recent studies demonstrate that MTV and TLG were computed using a maximum percentage threshold of 40-50% (30,31). However, other studies used a fixed SUV threshold, most commonly SUV2.5, where SUV>2.5 is the absolute threshold (TLG2.5 or MTV2.5), particularly for segmentation of lung tumors (32–34). Increasing interest in volumetric indices has led to the development of commercially available tools, for example PETVCAR, which enables the rapid and simple measurement of numerous indices for tumor analysis, including various threshold values of MTV and TLG (typically, 41-70% of SUV max within the tumor) (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, the current study showed the prognostic roles of OS and RFS in MTV only in univariate analysis. It is well known that pretreatment MTV and TLG are potent prognostic factors in various cancers [29,30,31]. Nevertheless, conflicting results regarding the prognostic role of sequential F-18 FDG PET/CT still exist in LAEC patients treated with preoperative CRT.…”
Section: Discussionmentioning
confidence: 99%
“…Results revealed that metabolic tumor volume and total lesion glycolysis are independent prognostic factors for predicting RFS and OS. Thus, 18 F-FDG PET/CT can provide useful prognostic information for patients undergoing resection of PC with curative intent irrespective of neoadjuvant treatment [46] . Choi et al [47] evaluated the prognostic value of 18 F-FDG PET in patients with resectable PC.…”
Section: Staging: Wang Et Almentioning
confidence: 99%